Assessing Carnivorous Plants for the Production of Recombinant Proteins - Miguel, Sissi; Nisse, Estelle; Biteau, Flore; Rottloff, Sandy; Mignard, Benoit; Gontier, Eric; Hehn, Alain; Bourgaud, Frédéric (Frontiers in Plant Science, 2019)
The recovery of recombinant proteins from plant tissues is an expensive and time-consuming process involving plant harvesting, tissue extraction, and subsequent protein purification. The downstream process costs can represent up to 80% of the total cost of production. Secretion-based systems of carnivorous plants might help circumvent this problem. Drosera and Nepenthes can produce and excrete out of their tissues a digestive fluid containing up to 200 mg. L-1 of natural proteins. Based on the properties of these natural bioreactors, we have evaluated the possibility to use carnivorous plants for the production of recombinant proteins. In this context, we have set up original protocols of stable and transient genetic transformation for both Drosera and Nepenthes sp. The two major drawbacks concerning the proteases naturally present in the secretions and a polysaccharidic network composing the Drosera glue were overcome by modulating the pH of the plant secretions. At alkaline pH, digestive enzymes are inactive and the interactions between the polysaccharidic network and proteins in the case of Drosera are subdued allowing the release of the recombinant proteins. For D. capensis, a concentration of 25 μg of GFP/ml of secretion (2% of the total soluble proteins from the glue) was obtained for stable transformants. For N. alata, a concentration of 0.5 ng of GFP/ml secretions (0.5% of total soluble proteins from secretions) was reached, corresponding to 12 ng in one pitcher after 14 days for transiently transformed plants. This plant-based expression system shows the potentiality of biomimetic approaches leading to an original production of recombinant proteins, although the yields obtained here were low and did not allow to qualify these plants for an industrial platform project.